SHARK - National marine environmental monitoring of Harbour porpoise in Sweden - SHARK SMHI (SMHI - Swedish Meteorological and Hydrological Institute, 2024)
The national monitoring program is financed by the Swedish Agency for Marine and Water Management.

Monitoring is performed by the Swedish Museum of Natural History. Data are stored in the Swedish Ocean Archive (SHARK) by the Swedish Meteorological and Hydrological Institute (SMHI).

Information about the program and the methods are available in Swedish at the website of Swedish Agency for Marine and Water Management, https://www.havochvatten.se/overvakning-och-uppfoljning/miljoovervakning/marin-miljoovervakning/tumlare.html
Keywords: Harbour porpoise; Samplingevent; Samplingevent; SAMPLING_EVENT; Biological Sciences; Biologi